Konsumsi dalam Ekonomi Islam - Ochi Nurlisa; Fitri Yanti; Arina Maisila; M.Yusuf Bahtiar (Indonesia Economic Journal, 2026)
Consumption is an economic activity inseparable from human life. From an Islamic economic perspective, consumption activities are not only oriented towards fulfilling needs and satisfaction but must also be based on sharia values. This article aims to analyze the concept of consumption in Islamic economics and the principles that govern it. The research method used is a qualitative literature study approach, reviewing various sources such as books, journals, and other relevant scientific references. The results of the discussion indicate that consumption in Islam emphasizes the principles of halal (permissible) and thayyib (good), the prohibition of excess (israf), and the importance of balancing individual needs and social responsibility. Therefore, the application of Islamic consumption principles is expected to create well-being that is not only material but also spiritual.